Durability properties of self compacting concrete partial replacement of fine aggregate with waste crushed glass. (2022) - Shiva Srikanth, K.; Lalitha, G.
Abstract: This research work presents the durability properties of self-compacting concrete partial substitution of sand with waste crushed glass. In SCC cement was replaced with Fly-ash (15%), Alccofine (20%) by weight of cementitious material. These binder proportions are fixed for all mixes. Waste crushed glass has sufficient amount of amorphous silica content which is easily substituted to fine aggregate in SCC. Proportions are taken to replace the fine aggregate with waste crushed glass was 0%, 10%, 20%, 30% and 40% by weight of sand in mix. Grade of the concrete prepared was M70 and W/C was taken as 0.3. In present research work acid attack test and half-cell potential were carried out. For Acid attack test cube specimens of size (100 mm × 100 mm × 100 mm) were casted and cured for 90 days, for half-cell potential test cylinders (200 mm × 100 mm) were casted and cured for 90 days. In acid attack test 5% of hydrochloric acid and sulfuric acid were taken for testing. The results of normal concrete and concrete with waste crushed glass are compared. Test results showing better performance with waste crushed glass in Sulfuric acid and Hydrochloric acid. With 40% waste crushed glass, specimens immersed in Sulfuric acid, weight loss and strength loss are 3.8% and 4.85% respectively by weight before immersed in Sulfuric acid. With 40% waste crushed glass, specimens immersed in Hydrochloric acid weight loss and strength loss are 2.56% and 6.08% respectively by weight before immersed in Hydrochloric acid. Half-cell potential test values are showing increasing the glass content corrosion of steel was decreasing.